Efecto de los reguladores de crecimiento vegetal y el endospermo líquido de coco en la supervivencia y proliferación de callos embriogenicos de aguaje (mauritia flexuosa l.f.) - Meléndez Pérez, Mitzi Angela (2012)
This research paper aimed General: Contribute to the development of a methodology in vitro clonal propagation of selected genotypes sexed seedlings of palm (Mauritia flexuosa Lf) in the Peruvian Amazon and Specific objectives: To establish a protocol for embryogenic callus multiplication palm (Mauritia flexuosa Lf), testing the effect of growth regulators plant survival and proliferation of embryogenic calluspalm (Mauritia flexuosa Lf) and evaluate the effect of liquid coconut endosperm proliferation of embryogenic calluspalm (Mauritia flexuosa Lf).As this is an observation al research, comparison of datawas performed using descriptive statistics and comparison with cumulative frequencies, together with bar and line graph in which each treatment had 10 replication seffect of response regulators plant growth and the liquid endosperm of coconut in the explants(zygotic embryos) aguaje. Were tested for growth media in order to multiply the embryogenic callus. Components studied were: 2,4-D (A0 = 0ppm= 25ppmA1, A2 = 45ppm, A3 =75ppm) and Coconut Water Rate(B0=0%,B1= 5%, B2=10%; B3 =20%). The most significant findings were: Treatments T2 (10%coconut water) and T3(20%coconut water) were those with less contamination by microorganisms with averages of16.67% and 0.0% respectively in treatments 2,4 D, T3 (75ppm), T2 (45ppm) did not suffer any pollution, but the treatmentsT1(25ppm) and T0(control) showed contamination rates of the order of41.67% and 66.67% respectively in the phenolization was observed from the 3rd assessment (14 days after the 2nd evaluation) where fenolizaron all treatments in the order of 25%, 25% and 100% for treatment T0(control), 41.67%, 50.0% and 100% for T1(5%coconut water), 41.67%, 58.33% and 100% for T2(10%coconut water)and41.67%, 50.0% and 100.0% for T3(20%coconut water) and42 days respectively for the second evaluation fenolizaron all treatments up to 100.0% in Q3 (20% coconut water) with a coefficient of variation of 19.9%, followed by T1(5% water coconut) with 22.89% and those who reached calluses average of 63.89% and 55.55% rated treatments as more stable in the evolution of embryogenic callus formation.